2021
DOI: 10.1002/ppul.25674
|View full text |Cite
|
Sign up to set email alerts
|

The improved clinical course of persistent tachypnea of infancy with inhaled bronchodilators and corticosteroids

Abstract: Background: Persistent tachypnea of infancy (PTI) is the most common interstitial lung disease in young children. As no standardized therapeutic guidelines exist, different pharmaceuticals are used to treat PTI; inhaled corticosteroids (ICS) and bronchodilators being mostly used. This observation assessed the effectiveness of bronchodilators and ICS in children with PTI enrolled in the children's interstitial lung diseases (chILD)-EU Register.Methods: Symptomatic children with PTI were observed according to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 41 publications
0
2
0
1
Order By: Relevance
“…The vast majority of published data refer to children with asthma and cystic fibrosis. 33 IOS is particularly useful in young children because it requires minimal cooperation. 34 Our study showed that all IOS indexes reflecting small airway function (i.e., R5, R5-R20, F res , and AX) were significantly higher in PTI patients when compared with healthy controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The vast majority of published data refer to children with asthma and cystic fibrosis. 33 IOS is particularly useful in young children because it requires minimal cooperation. 34 Our study showed that all IOS indexes reflecting small airway function (i.e., R5, R5-R20, F res , and AX) were significantly higher in PTI patients when compared with healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Also, new techniques such as IOS and N2MBW have not yet been used in the assessment of lung function in children with PTI despite the fact that there is a growing number of studies demonstrating the usefulness of IOS for evaluating peripheral airways. The vast majority of published data refer to children with asthma and cystic fibrosis 33 . IOS is particularly useful in young children because it requires minimal cooperation 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Existe un único estudio observacional y prospectivo, que se realizó en 31 pacientes, reportó mejoría en la gravedad de los síntomas y de la función pulmonar tras la administración de broncodilatadores y corticoides inhalados (19).…”
Section: Opciones Terapéuticasunclassified